PENGEMBANGAN BĪ’AH LUGHAWIYYAH OLEH HIMPUNAN MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB DI IAIN PEKALONGAN - M Fairuz Rosyid (Fakultas Tarbiyah dan Keguruan UIN Sunan Gunung Djati Bandung, 2020)
This article aims to develop the bī'ah lughawiyyah carried out by the Student Association of the Arabic Language Education Institute of the State Islamic Institute of Pekalongan. This research focuses on the bī'ah lughawiyyah model in terms of the purpose of the bī'ah lughawiyyah, the forms of activities, and the learning model in the bī'ah lughawiyyah. This research method is qualitative, using interviews, observation, and documentation techniques. Data were analyzed using Miles and Huberman analysis. The perspective in this study is the theory of language environment proposed by Stephen D. Krashen. The results of this study indicate that the development model of bī'ah lughawiyyah based on